2014
DOI: 10.4172/2327-4972.1000140
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Quality and Determinant Factors of Post-Abortion Care in Governmental Hospitals of Tigray, Ethiopia, 2013

Abstract: Background: Unsafe abortion is one of the leading causes of maternal mortality and morbidity worldwide accounting for 13% of maternal deaths globally.Objective: To assess quality and determinant factors of post-abortion care in governmental Hospitals of Tigray, Ethiopia. Method:Institution based Cross-sectional study was conducted from January to May 2013. Four hundred twenty post apportion care clients were interviewed and 60 clients were observed to obtain qualitative data. Data was collected using pre prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
13
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 12 publications
5
13
2
3
Order By: Relevance
“…The use of invasive methods such as dilation and curettage (especially for first‐trimester evacuation procedures) raises concern over the adherence to guidelines, as well as the process through which service providers decide on treatment and the factors that inform the decision. The present finding differs from past studies, which showed that dilation and curettage equipment were available in healthcare facilities yet remained unused . Interestingly, almost all dilation and curettage cases recorded in the IMUA study occurred at level‐4–5 private facilities .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The use of invasive methods such as dilation and curettage (especially for first‐trimester evacuation procedures) raises concern over the adherence to guidelines, as well as the process through which service providers decide on treatment and the factors that inform the decision. The present finding differs from past studies, which showed that dilation and curettage equipment were available in healthcare facilities yet remained unused . Interestingly, almost all dilation and curettage cases recorded in the IMUA study occurred at level‐4–5 private facilities .…”
Section: Discussioncontrasting
confidence: 99%
“…The present finding differs from past studies, which showed that dilation and curettage equipment were available in healthcare facilities yet remained unused. 19 Interestingly, almost all dilation and curettage cases recorded in the IMUA study occurred at level-4-5 private facilities. 16 Use of appropriate technology for PAC in the first and second trimesters can be seen against the backdrop of high cost of some of the highly invasive and inappropriate procedures such as dilation and curettage.…”
Section: Discussionmentioning
confidence: 96%
“…This is supported with findings done in Oromia and Amhara region in which 53.4% left the health facility by concealing about family planning and 44% received appropriate information and returned with different contraception methods [29]. This is also supported by a study in Guragea in which about 56.5% and in Tigray about 48% of participants were received accurate information and postabortion family planning [23,28].…”
Section: Discussionsupporting
confidence: 79%
“…The possible reason for the similarity could be due to the similarity in the study subjects and the similarity of socio-demographic and culture of the study subjects in both studies. But the finding is higher than the findings from Mexico 24%, Tanzania (20%), in Tigray (40.6%), in Oromia and Amhara region (79.6%), Jimma (76.3%), and Adis Ababa (60.5%) [25][26][27][28][29][30]. The possible reason for the discrepancy might be due to the variation in the sample size, study subjects, sampling methods, and sociocultural and demographic background of the study subjects.…”
Section: Discussionmentioning
confidence: 89%
“…This was confirmed by Perera et al and Yegon et al that stigma and poverty, nonetheless, also played a vital role in influencing the decision-making process [ 6 41 ]. Demtsu et al reported an association between the provision of PAC services, religious, cultural beliefs, morals, and values in terms of care of women seeking PAC services [ 42 ].…”
Section: Discussion Of Findingsmentioning
confidence: 99%